PRACTICES OF IMPLEMENTING MUSEUM PROJECTS WITH THE UKRAINIAN CULTURAL FOUNDATION’S SUPPORT: PROBLEMS AND RECOMMENDATIONS - Shershnova, Olena; Bryzhuk, Andrii (Public Management and Policy, 2025)
The article provides a comprehensive analysis of the implementation of museum projects supported by the Ukrainian Cultural Foundation, aiming to identify key institutional, regulatory, and managerial barriers that prevent museums from fully participating in grant competitions. The relevance of the study is determined by Ukraine’s European integration course, the need to modernize the cultural sector and strengthen the role of museums as outposts for preserving heritage and building national resilience in the context of full-scale war. The study aims to identify and systematize the patterns of success, regional distribution and institutional problems of museum initiatives supported by the UCF. The methodological basis comprises a systematic and comparative analysis of the regulatory and legal framework, as well as an empirical analysis of the UCF’s rating lists and project registers for the period 2018–2025. Quantitative methods were used to calculate the share of successful applications and track regional distribution, as well as a case study method for in-depth analysis of the partnership model for project implementation. The main results show that, despite the UCF’s catalytic role in stimulating digitalization, inclusiveness and innovation in the museum sector, the direct competitiveness of state and municipal museums remains low. This is due to limited financial autonomy, complex budgetary and treasury procedures, as well as low institutional capacity and staff shortages. As a result, the partnership model (“civil society organization as executor – museum as partner”) dominates, covering about 80% of successful museum initiatives, providing flexibility but not solving the problems of systemic reform. Significant regional unevenness in the distribution of projects has been identified. It has been established that museum projects that are structurally “rigid” (exhibitions, digitization) are structurally losing out to “mixed” (event-based, educational) projects within the existing UCF lots. The conclusions emphasize the critical need for systemic reform of the legal status of museums to increase their financial autonomy. Further research should focus on developing specific proposals for the creation of a specialized grant lot for “hard” museum projects within the structure of the UCF, which is a necessary condition for ensuring their sustainability and full participation in Ukraine’s cultural policy.